2015
DOI: 10.5194/bg-12-6369-2015
|View full text |Cite
|
Sign up to set email alerts
|

Halocarbon emissions and sources in the equatorial Atlantic Cold Tongue

Abstract: Abstract.Halocarbons from oceanic sources contribute to halogens in the troposphere, and can be transported into the stratosphere where they take part in ozone depletion. This paper presents distribution and sources in the equatorial Atlantic from June and July 2011 of the four compounds bromoform (CHBr 3 ), dibromomethane (CH 2 Br 2 ), methyl iodide (CH 3 I) and diiodomethane (CH 2 I 2 ). Enhanced biological production during the Atlantic Cold Tongue (ACT) season, indicated by phytoplankton pigment concentrat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(41 citation statements)
references
References 99 publications
2
33
6
Order By: Relevance
“…We compare with cruises and open ocean estimates, since OASIS mainly covered open ocean regions and only small coastal areas close to Madagascar, the British Indian Ocean Territory, and the Maldives. The average CHBr 3 emission during the OASIS campaign (910 pmol m −2 h −1 ) was larger than during most campaigns in tropical regions: 1.5 times larger than during TransBrom in the subtropical and tropical west Pacific (Tegtmeier et al, 2012), 1.2 times larger than during DRIVE in the tropical northeast Atlantic (Hepach et al, 2014), and 1.5 times larger than during MSM18/3 in the Atlantic equatorial upwelling (Hepach et al, 2015). Only the SHIVA campaign in the South China and Sulu seas yielded larger CHBr 3 emissions of 1486 pmol m −2 h −1 because of very high oceanic concentrations close to the coast (Fuhlbrügge et al, 2016b).…”
Section: Comparison Of Oasis Vsls Emissions With Other Oceanic Regionsmentioning
confidence: 68%
See 3 more Smart Citations
“…We compare with cruises and open ocean estimates, since OASIS mainly covered open ocean regions and only small coastal areas close to Madagascar, the British Indian Ocean Territory, and the Maldives. The average CHBr 3 emission during the OASIS campaign (910 pmol m −2 h −1 ) was larger than during most campaigns in tropical regions: 1.5 times larger than during TransBrom in the subtropical and tropical west Pacific (Tegtmeier et al, 2012), 1.2 times larger than during DRIVE in the tropical northeast Atlantic (Hepach et al, 2014), and 1.5 times larger than during MSM18/3 in the Atlantic equatorial upwelling (Hepach et al, 2015). Only the SHIVA campaign in the South China and Sulu seas yielded larger CHBr 3 emissions of 1486 pmol m −2 h −1 because of very high oceanic concentrations close to the coast (Fuhlbrügge et al, 2016b).…”
Section: Comparison Of Oasis Vsls Emissions With Other Oceanic Regionsmentioning
confidence: 68%
“…Oceanic upwelling occurs along the eddy-rich, shallow region south of Madagascar, which leads to locally enhanced phytoplankton growth (Quartly et al, 2006). It is possible that an upwelling of elevated CH 2 Br 2 concentrations from the deeper ocean could have occurred in a similar way as was observed for the equatorial upwelling in the Atlantic (Hepach et al, 2015). CH 3 I oceanic concentrations range from 0.2 to 16.4 pmol L −1 , with a mean of 3.4 ± 3.1 pmol L −1 .…”
Section: Vsls Observations and Oceanic Emissionsmentioning
confidence: 86%
See 2 more Smart Citations
“…Recent studies have identified open-ocean upwelling areas in the Atlantic as large source regions for a number of brominated and iodinated oceanic trace gases (Quack et al, 2004(Quack et al, , 2007O'Brien et al, 2009;Raimund et al, 2011;Hepach et al, 2015). Their sources are related to biological and chemical processes in the productive waters of the upwelling.…”
Section: Introductionmentioning
confidence: 99%